El Pliensbachiense de la Rama Aragonesa de la Cordillera Ibérica: Análisis de facies y establecimiento de secuencias - Bordonaba, A. P.; Aurell, M. (Journal of Iberian Geology, 2002)
The Pliensbachian of the Aragonese branch of the Iberian Chain is represented by Almonacid de la Cuba, Cerro del Pez and Barahona formations. These sediments are constituted by marls and limestone organized in shallowingupward sequences. All of them are represented in the lower part by marls and mudstone that change to wackestone and packstone. The top of the sequence is a ferruginous crust, generally bioturbated. This represents the decrease in the sedimentation velocity and a shallowing event. The sediments were deposited in a carbonate ramp, changing from middle to outer environments. The most shallowing facies were located in the south, where there is an evidence of the developing of reefal facies. The deeper facies were deposited in the north, corresponding to open environments. This work shows the correlation of six thirdorder shallowing upward sequences in the Pliensbachian sediments. The origin of these sequences is related to sea level oscillations and conditioned by autocyclic processes.
Keywords: Pliensbachian; Shallowing-upward sequences; Carbonate ramp; Iberian Chain